ApbZIP2-mediated enhancement of lipid productivity supports sustainable plant-based omega-3 biomanufacturing - Rong Zhou; Kairui Mu; Ya’nan Shi; Yuqin Li; Liwen Luo; Yunkai Tan; Zhenyao Wang; Yufang Tang; Xuan Li (Bioresource Technology, 2027)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Removal efficiency and mechanisms of natural mineral materials for bacteriophages MS2 and ΦX174 in aqueous environments - Ying Song; Ya-ting Wang; Ying Han; Rong-xuan Xu; Yang Wang; Shuang Xu; Ming-da Liu (Journal of Contaminant Hydrology, 2026)

Divergent responses of ecosystem water use efficiency to environmental drivers in arid versus humid regions - Hailing Li; Maohong Wei; Hongling Yang; Ya Hu; Shaokun Wang; Ping Yue; Xujun Ma; Fangwei Hao; Rong Ma; Xiaoan Zuo (Journal of Environmental Management, 2026)

In-situ generation and activation of H2O2 by synergistic dipole moment and multi-metal cycle for piezo-photocatalytic water cleanup - Zheng-Tao Dong; Long Sui; You Wu; Xiao-Ju Wen; Ya-Ya Yang; Yan-Rong Chen; Wen-Jun Wang; Hai Guo (Chemical Engineering Journal, 2026)

Oxygen mass transfer characteristics of different hollow-fiber bubble-free aeration membranes via clean water oxygenation tests under different aeration and measurement modes - Zhe Yuan; Chun-Hai Wei; Jing-Su Liu; Zhi-Wei Lian; Jing-Yin Wang; Hua-Rong Yu; Hong-Wei Rong; Zhi-Hui Pan; Zhong-Lin Nie; Ya-Song Chen; Xia Huang (Water Research, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Dysregulated KIF2A correlates with p53 expression pattern in breast cancer - Yun Hao; Si-Qin Ma; Ting Xu; Jia-Qi Wu; Rong Ma; Ya-Wen Wang; Jian-Li Wang (Molecular and Cellular Biochemistry, 2026)

Diversity and taxonomic revision of Hoya (Apocynaceae, Asclepiadoideae) in China based on morphological and molecular evidence - Yang Liu; Wang Xi; Nie-Rong Lu; Ji-Dong Ya; Jing-Feng Zhang; Lei Cai (Plant Systematics and Evolution, 2026)

Photoelectron-driven modulation of carbon metabolism enhances hydrogen production in a ZnIn2S4-Shewanella oneidensis biohybrid system - Xue-Meng Wang; Hao-Yu Li; Kai-Li Wang; Zhi-Xuan Zhang; Yu-Xin Cao; Ya-Lian Ma; Rong Chen (Bioresource Technology, 2026)

Genome-wide identification and promoter activity analysis of fibrillin gene families in different color carrot roots - Yu-Jie Sun; Rong-Rong Zhang; Zi-Han Zhao; Xu Zhang; Xue-Feng Peng; Ya-Hui Wang; Ai-Sheng Xiong (Protoplasma, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Cold adaptation strategies of anammox bacteria and the bottleneck of nitrogen removal performance in autotrophic nitrogen removal process treating digested swine wastewater - Ya-hui Wang; Fang-yu Huang; Long-xing Jiang; Rong You; Yun-hong Zhang; Liang-wei Deng; Wen-guo Wang; Lan Wang (Chemical Engineering Journal, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Glutamine-hydrolyzing GMP Synthase Gene (guaA) Regulates Siderophore Synthesis in the Nitrogen-fixing Bacterium (NFB) Kosakonia radicincitans GXGL-4A - Er-Xing Wang; Bao-Yun Feng; Ya-Ting Zhang; Meng-Ting Zhang; Lu-Rong Xu; Yan-Wen Xue; Yun-Peng Chen (Current Microbiology, 2026)

Reversing the paradigm: Oxygen-dependent switch of nTiO₂ from promoting to suppressing ARG conjugation - Jie Yu; Xin Wang; Ya-Xin Hu; Feng-Ting Cao; Qiu-Rong Zhang; Xiang-Tong Zhou; Xiang Xiao (Journal of Hazardous Materials, 2025)

The critical role of mitophagy in cell senescence-mediated pulmonary fibrosis and potential therapeutic strategies - Xing-Yi Chen; Dong-Mei Wang; Ya Zhou; Li Liu; Tao Zhu; Zhao Ran; Mei-Hong Lu; Ben-Rong Mu (Molecular Biology Reports, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

A strain of mycovirus AaVV1 mediates hypovirulence of Alternaria species - Ya Rong Wang; Yi Chen; Chang Xin Li; Xiao Gang Li; Jun Zi Zhu; Jie Zhong (Pesticide Biochemistry and Physiology, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Fluoride Induces Spermatogonial Apoptosis via IP3R-MCU-Mediated Mitochondrial Calcium Overload - Rong Wang; Han Wang; Wenjing Gong; Xiaoqian Chen; Mengli Zheng; Ya Cui; Chunmei Liang; Jiayue Hu; Yuanhua Chen; Yanli Ji (Biological Trace Element Research, 2025)

Computational profiling and virtual screening of MEK inhibitors for triple-negative breast cancer therapy - Ya-Kun Zhang; Jian-Bo Tong; Rong Wang; Wen Tian; Yan-Rong Zeng (In Silico Pharmacology, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Molecular characterization of a novel chrysovirus isolated from the phytopathogenic fungus Fusarium commune - Wen Xin Huang; Li E Yang; Yan Bin Huang; Tao Sha Xu; Jie Zhong; Ya Rong Wang; Yan Song Xiao (Archives of Virology, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Machine learning-based design, screening, and activity validation of topoisomerase I inhibitors - Ya-Kun Zhang; Jian-Bo Tong; Jia-Le Li; Rong Wang; Yan-Rong Zeng (Molecular Diversity, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

A critical review on pear Fruit’s polyphenols and its chlorogenic acid: Composition, bioavailability, and pharmacological potential - Abdul Basit; Raheem Shahzad; Abdul Mueed; Asim Muhammad; Wang Rong; Liu Ya; Gong Xin; Khanizadeh Shahrokh; Muhammad Arshad; Tao Shutian (Food Bioscience, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Preparation of sodium alginate/pectin/cellulose nanofibrils films containing black soybean seed coat anthocyanins for monitoring goat meat freshness - Siying Wang; Xinyue Han; Ya Chen; Yikai Shao; Jiaqing Song; Chunjie Yang; Shengqi Jiang; Rong Bai; Xiang Ye; Wu Ding (Food Control, 2025)

Genomic characterization of a novel gammapartitivirus infecting the phytopathogenic fungus Colletotrichum cliviicola - Ya Rong Wang; Jie Zhong; Zhijuan Yang; Yi Chen; Jia En Su (Archives of Virology, 2025)

Two novel mitoviruses coinfecting the fungus Colletotrichum karstii - Wei Zhang; Jie Zhong; Jun Zi Zhu; Yi Chen; Ya Rong Wang (Archives of Virology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

DcNCED2 promotes ABA synthesis via carotenoid degradation and enhances drought resistance in carrot - Rong-Rong Zhang; Ya-Hui Wang; Xue-Feng Peng; Yu-Jie Sun; Nan Zhang; Ai-Sheng Xiong (Plant Cell Reports, 2025)

A comparative study of four color measurement methods for soil color identification and related properties prediction - Yuanyuan Du; Fengjin Kang; Zhangke Huang; Luyi Wang; Ya Zhang; Decheng Li; Guanghui Zheng; Rong Zeng (Computers and Electronics in Agriculture, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Engineered multienzyme-mimicking 2D bismuthene catalytic nanotriggers enable cascade enzyodynamic-boosted and synergistic GPX4/FSP1-mediated ferroptosis amplification for cancer radiosensitization - Yipengchen Yin; Li Zhu; Tiaoyan Jiang; Rong Chai; Ya Zhang; Tianyu Li; Kai Wang; Sheng Wang; Qin Zhang (Chemical Engineering Journal, 2024)

Genomic characteristics of a novel non-segmented double-stranded RNA mycovirus from the fungus Nigrospora oryzae - Ya Rong Wang; Jie Zhong; Tian Bo Liu; Yan Song Xiao (Archives of Virology, 2024)

FGTN: Fragment-based graph transformer network for predicting reproductive toxicity - Jia-Nan Ren; Qiang Chen; Hong-Yu-Xiang Ye; Cheng Cao; Ya-Min Guo; Jin-Rong Yang; Hao Wang; Muhammad Zafar Irshad Khan; Jian-Zhong Chen (Archives of Toxicology, 2024)

Impact of a Potent Strain of Plant Growth-Promoting Bacteria (PGPB), Bacillus subtilis S1 on Bacterial Community Composition, Enzymatic Activity, and Nitrogen Content in Cucumber Rhizosphere Soils - Meng-Ting Zhang; Yu-Qing Bao; Bao-Yun Feng; Lu-Rong Xu; Ya-Ting Zhang; Er-Xing Wang; Yun-Peng Chen (Current Microbiology, 2024)

A potential trade-off between reproduction and enhancement of thermotolerance in Liriomyza trifolii populations driven by thermal acclimation - Yu-Cheng Wang; Ya-Wen Chang; Fei Yang; Wei-Rong Gong; Jie Hu; Yu-Zhou Du (Journal of Thermal Biology, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

The cytochrome P450 gene CYP4g1 driven by high temperature confers abamectin tolerance on Liriomyza trifolii through promoting cuticular hydrocarbons biosynthesis - Yu-Cheng Wang; Ya-Wen Chang; Hong-Fang Xie; Wei-Rong Gong; Cheng-Dong Wu; Yu-Zhou Du (Pesticide Biochemistry and Physiology, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Novel insights into dimethylsulfoniopropionate cleavage by deep subseafloor fungi - Xuan Liu; Xin-Ran Wang; Fan Zhou; Ya-Rong Xue; Xiang-Yang Yu; Chang-Hong Liu (Science of The Total Environment, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

New diterpenoid alkaloids from Delphinium pachycentrum Hemsl - Yuan-Feng Yan; Ya-Rong Wang; Hong-Jun Jiang; Zong-Bao Ding; Tian-Peng Yin (Natural Product Research, 2024)

Modifying duck myofibrillar proteins using sodium bicarbonate under cold plasma treatment: Impact on the conformation, emulsification, and rheological properties - Shengqi Jiang; Chunjie Yang; Rong Bai; Ziwei Li; Linlu Zhang; Ya Chen; Xiang Ye; Siying Wang; Hao Jiang; Wu Ding (Food Hydrocolloids, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Dietary creatine promotes creatine reserves, protein deposition, and myofiber hyperplasia in muscle of juvenile largemouth bass (Micropterus salmoides) - Haodong Yu; Ya He; Mu Qin; Li Wang; Keming Rong; Xuezhen Zhang (Aquaculture, 2024)

Artificial infection pathway of largemouth bass LMBV and identification of resistant and susceptible individuals - Ya Zhang; Bin Gui; Zhihui Jia; Yongming Li; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Impact of environmental supervision reform on green innovation in mineral enterprises - Jingshen Zhang; Xinzhu Zhou; Rong Bai; Haoyang Dong; Tingting Tang; Zeyu Wang; Ya Yang; Feng Huang (Resources Policy, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Metal-organic framework composite Mn/Fe-MOF@Pd with peroxidase-like activities for sensitive colorimetric detection of hydroquinone - Die Deng; Ya Wang; Shaohua Wen; Yujie Kang; Xiaoyan Cui; Rong Tang; Xiupei Yang (Analytica Chimica Acta, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Effects of anti-pull ties on the bearing behaviors of shallow tunnel-type anchorages in soft rock - Ya-feng Han; Xin-rong Liu; Erdi Abi; Yi-liang Tu; Bin Xu; Xiao-han Zhou; Zhi-yun Deng; Zhong-hao Wang (Journal of Mountain Science, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Dauer larva-derived extracellular vesicles extend the life of Caenorhabditis elegans - Jing Ma; Yi-ting Wang; Ling-hui Chen; Bang-ya Yang; Yong-zhu Jiang; Lan-xi Wang; Zhi-qi Chen; Guan-rong Ma; Liao-qiong Fang; Zhi-biao Wang (Biogerontology, 2023)
There is growing evidence that extracellular vesicles (EVs) play a functional role in tissue repair and anti-aging by transferring the contents of donor cells to recipient cells. We hypothesized that Dauer ( C. elegans ), known as “ageless” nematodes, can also secrete extracellular vesicles and influence the lifespan of C. elegans . Here, we isolated EVs of dauer larvae (dauer EVs). Dauer EVs were characterized using transmission electron microscopy, nanoparticle tracking analysis (NTA), and Western blot analysis. Wild-type C. elegans were fed in the presence or absence of dauer EVs and tested for a range of phenotypes, including longevity, mobility and reproductive capacity. Results showed that dauer EVs increased the average lifespan of nematodes by 15.74%, improved mobility, slowed age-related pigmentation as well as body length, and reduced the accumulation of reactive oxygen species and lipids, while not impairing nematode reproductive capacity. These findings suggest that dauer EVs can extend the lifespan of C. elegans as well as the healthy lifespan by reducing ROS accumulation, with potential anti-aging capacity.

A new butenolide with antifungal activity from solid co-cultivation of Irpex lacteus and Nigrospora oryzae - Ya-Mei Wu; Xue-Qiong Yang; Jing-Xin Chen; Ting Wang; Tai-Ran Li; Fan-Rong Liao; Run-Tong Liu; Ya-Bin Yang; Zhong-Tao Ding (Natural Product Research, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

Assessing the Coordinate Development Between Economy and Ecological Environment in China’s 30 Provinces from 2013 to 2019 - Bing Rong; Cheng-jun Chu; Zhen Zhang; Ya-ting Li; Shu-hao Yang; Qian Wang (Environmental Modeling & Assessment, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Cumulative effects of temperature on blood pressure during pregnancy: A cohort study of differing effects in three trimesters - Qi Chen; Ya Wang; Hui-Rong Tang; Yuan Wang; Ai-Hua Gu; Xiang-Jun Zhai; Ming-Ming Zheng (Science of The Total Environment, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

An approach to the high efficient exploitation of nature gas hydrate and carbon sequestration via injecting CO2/H2 gas mixture with varying composition - Bo-Jian Cao; Yi-Fei Sun; Hong-Nan Chen; Jin-Rong Zhong; Ming-Long Wang; Meng-Ya Niu; Jing-Yu Kan; Chang-Yu Sun; Dao-Yi Chen; Guang-Jin Chen (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Plastid diversity and chromoplast biogenesis in differently coloured carrots: role of the DcOR3Leu gene - Yu-Min Zhang; Rong-Hua Wu; Lu Wang; Ya-Hui Wang; Hui Liu; Ai-Sheng Xiong; Zhi-Sheng Xu (Planta, 2022)

Silencing circ_0074371 inhibits the progression of sepsis-induced acute kidney injury by regulating miR-330-5p/ELK1 axis - Qiu-yuan Wang; Rong-rong Zhang; Long Cui; Ya-ping Sun (Mammalian Genome, 2022)

Dynamic Cause of the Sudden Death Event of Small Yellow Croaker (Larimichthys polyactis) in the East China Sea in Winter 2017 - Zilu Wei; Xiaohui Jiao; Jicai Zhang; Yunfei Du; Zengrui Rong; Hui Wu; Ya Ping Wang (Frontiers in Marine Science, 2022)
Small yellow croaker ( Larimichthys polyactis ), a benthic fish species widely distributed in the Northwest Pacific Ocean, plays an important role in the fishery catch of coastal countries. A large amount of dead small yellow croaker floated on the sea surface near 30.2°N, 125.3°E in the East China Sea on 19 February 2017, and more than 9,000 kilograms were caught by fishermen, which had never been recorded before. This study aims to investigate the dynamic causes of this sudden death event based on available in-situ, satellite and modelling data. The event occurred near the overwintering ground of small yellow croaker, where a majority of these fish assembled in winter. There were persistent ocean fronts at target site with average intensity of 0.05°C/km at sea surface and bottom in February 2017, which was the strongest in the past 5 years from 2015 to 2019. The fronts provided nutrients and food to fish, and the intense gradients prevented fish from crossing, thus forming “water barriers” to restrict the horizontal movement of fish. Due to enhanced convection, the water was well-mixed, enabling the demersal croaker to float to sea surface. The sea temperature was particularly warm in winter 2017, but then experienced a significant drop by more than 4.5°C in 40 days according to satellite and modelling datasets due to the northerly wind and the southeastward movement of cold eddy. The drop of temperature led to ‘cold shock’ of fish, affecting their physiological regulation and survival. Under the combined influence of these factors, a large number of small yellow croaker died and aggregated near the target site. This paper has a great reference value for further study on the living habits of small yellow croaker and their responses to marine dynamic changes.

Two new species of Ceriporia (Irpicaceae, Basidiomycota) from the Asia Pacific area - Jia-Jia Chen; Ya-Rong Wang; Chao-Ge Wang; Yu-Cheng Dai (Mycological Progress, 2022)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Carbon monoxide-triggered health effects: the important role of the inflammasome and its possible crosstalk with autophagy and exosomes - Rong-Jane Chen; Yu-Hsuan Lee; Tzu-Hao Chen; Yu-Ying Chen; Ya-Ling Yeh; Ching-Ping Chang; Chien-Cheng Huang; How-Ran Guo; Ying-Jan Wang (Archives of Toxicology, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

The Joubert Syndrome Gene arl13b is Critical for Early Cerebellar Development in Zebrafish - Jian Zhu; Han-Tsing Wang; Yu-Rong Chen; Ling-Ya Yan; Ying-Ying Han; Ling-Yan Liu; Ying Cao; Zhi-Zhi Liu; Hong A. Xu (Neuroscience Bulletin, 2020)
Joubert syndrome is characterized by unique malformation of the cerebellar vermis. More than thirty Joubert syndrome genes have been identified, including ARL13B . However, its role in cerebellar development remains unexplored. We found that knockdown or knockout of arl13b impaired balance and locomotion in zebrafish larvae. Granule cells were selectively reduced in the corpus cerebelli, a structure homologous to the mammalian vermis. Purkinje cell progenitors were also selectively disturbed dorsomedially. The expression of atoh1 and ptf1 , proneural genes of granule and Purkinje cells, respectively, were selectively down-regulated along the dorsal midline of the cerebellum. Moreover, wnt1 , which is transiently expressed early in cerebellar development, was selectively reduced. Intriguingly, activating Wnt signaling partially rescued the granule cell defects in arl13b mutants. These findings suggested that Arl13b is necessary for the early development of cerebellar granule and Purkinje cells. The arl13b -deficient zebrafish can serve as a model organism for studying Joubert syndrome.

Brief report of the first cured 2019-nCoV pneumonia patient in West China Hospital - En-Qiang Chen; Li-Chun Wang; Guang-Min Tang; Yao Yang; Min-Jin Wang; Rong Deng; Fang Chen; Meng-Lan Wang; Ya-Chao Tao; Ping Feng; Hong Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

Transcript profiling of genes involved in carotenoid biosynthesis among three carrot cultivars with various taproot colors - Ya-Hui Wang; Tong Li; Rong-Rong Zhang; Ahmed Khadr; Yong-Sheng Tian; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

SsHKT1;1 is coordinated with SsSOS1 and SsNHX1 to regulate Na+ homeostasis in Suaeda salsa under saline conditions - Wen-Ying Wang; Ya-Qi Liu; Hui-Rong Duan; Xiu-Xia Yin; Yan-Nong Cui; Wei-Wei Chai; Xin Song; Timothy J. Flowers; Suo-Min Wang (Plant and Soil, 2020)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Transcriptome analysis of differentially expressed genes in rabbits’ ovaries by digital gene-expression profiling - Tao Huang; Ya-dong Wang; Ming-ming Xue; Xue Feng; Cai-Xia Sun; An-si Wang; Shu-yu Xie; Meng Zhang; Gui-Rong Sun; Ming Li (Genes & Genomics, 2018)

Inhibitory Effect of Vaginal Lactobacillus Supernatants on Cervical Cancer Cells - Ke-Di Wang; Dong-Jiang Xu; Bao-Ya Wang; Dong-Hui Yan; Zhi Lv; Jian-Rong Su (Probiotics and Antimicrobial Proteins, 2018)

Discovery of a novel multifunctional carbazole–aminoquinoline dimer for Alzheimer's disease: copper selective chelation, anti-amyloid aggregation, and neuroprotection - Xiao Zhang; Ying Wang; Sheng-nan Wang; Qiu-he Chen; Ya-lin Tu; Xiao-hong Yang; Jing-kao Chen; Jin-wu Yan; Rong-biao Pi; Yan Wang (Medicinal Chemistry Research, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

CNN-SVM for Microvascular Morphological Type Recognition with Data Augmentation - Di-Xiu Xue; Rong Zhang; Hui Feng; Ya-Lei Wang (Journal of Medical and Biological Engineering, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Improving the antioxidant activity and enriching salvianolic acids by the fermentation of Salvia miltiorrhizae with Geomyces luteus - Yun Xing; Le Cai; Tian-peng Yin; Yang Chen; Jing Yu; Ya-rong Wang; Zhong-tao Ding (Journal of Zhejiang University-SCIENCE B, 2016)

A highly efficient grapevine mesophyll protoplast system for transient gene expression and the study of disease resistance proteins - Feng-Li Zhao; Ya-Juan Li; Yang Hu; Yu-Rong Gao; Xue-Wen Zang; Qin Ding; Yue-Jin Wang; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

MALDI-TOF MS analysis of the extracellular polysaccharides released by the diatom Thalassiosira pseudonana under various nutrient conditions - Xin-Xin Ai; Jun-Rong Liang; Ya-Hui Gao; Samuel Chun-Lap Lo; Fred Wang-Fat Lee; Chang-Ping Chen; Chun-Shan Luo; Chao Du (Journal of Applied Phycology, 2015)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Anti-apoptosis effect of polysaccharide isolated from the seeds of Cuscuta chinensis Lam on cardiomyocytes in aging rats - Shou-Li Sun; Li Guo; Ya-Chao Ren; Bing Wang; Rong-Hui Li; Yu-Shan Qi; Hui Yu; Nai-Dan Chang; Ming-Hui Li; Hai-Sheng Peng (Molecular Biology Reports, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Assessing the real value of farmland in China - Rong Hu; Dao-chi Qiu; De-ti Xie; Xin-ya Wang; Lin Zhang (Journal of Mountain Science, 2014)

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

MiR-26a regulates cell cycle and anoikis of human esophageal adenocarcinoma cells through Rb1-E2F1 signaling pathway - Ya-Fei Zhang; An-Ran Zhang; Bi-Cheng Zhang; Zhi-Guo Rao; Jian-Fei Gao; Mu-Han Lv; Yu-Yun Wu; Su-Min Wang; Rong-Quan Wang; Dian-Chun Fang (Molecular Biology Reports, 2013)

Volatile profile analysis and quality prediction of Longjing tea (Camellia sinensis) by HS-SPME/GC-MS - Jie Lin; Yi Dai; Ya-nan Guo; Hai-rong Xu; Xiao-chang Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat - Mei-rong Zhao; Yang-yang Han; Ya-nan Feng; Feng Li; Wei Wang (Plant Cell Reports, 2012)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Endophytic fungus Cladosporium cladosporioides LF70 from Huperzia serrata produces Huperzine A - Zhi Bin Zhang; Qing Gui Zeng; Ri Ming Yan; Ya Wang; Zheng Rong Zou; Du Zhu (World Journal of Microbiology and Biotechnology, 2011)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Curcumin prevents liver fibrosis by inducing apoptosis and suppressing activation of hepatic stellate cells - Jian-Chang Shu; Ya-Jun He; Xia Lv; Guo-Rong Ye; Le-Xin Wang (Journal of Natural Medicines, 2009)

Sorption of 1,1,1-trichloro-2,2-bis(p-chlorophenyl) ethane (DDT) by clays and organoclays - Rong-Ling Dai; Gang-Ya Zhang; Xiao-Zhi Gu; Ming Kuang Wang (Environmental Geochemistry and Health, 2008)

Settlement, growth and survival of abalone, Haliotis discus hannai, in response to eight monospecific benthic diatoms - Rong-lian Xing; Chang-hai Wang; Xue-bin Cao; Ya-qing Chang (Journal of Applied Phycology, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)